Wood Micro-structural Studies of Indian Rutaceae Part I : Tribe Clauseneae - Bhardwaj, Nisha; Gupta, Sangeeta (Indian Forester, 2008)
The present study deals with the detailed wood anatomy of the 8 Indian species of 4 genera viz. Micromelum Bl., Glycosmis Correa, Clausenea Burm. and Murraya Linn. belonging to the tribe Clauseneae of the family Rutaceae. The results are summarized in the tables and identification key has been developed for the separation of all the 8 species of this tribe. Photomicrographs have been given for the diagnostic features. The woods of this tribe are used for carving, turnery and mathematical instruments. The wood anatomical parameters suggest that the tribe Clauseneae is a homogeneous tribe characterized by diffuse porous woods; growth ring distinct due to marginal bands of parenchyma; simple perforation plate; coalescent aperture in few vessels; fibres non-septate. Almost all type of parenchyma are covered these species. Rays homogeneous to heterogeneous. Prismatic crystals are present in fibres of Glycosmis winitii, Clausena excavata, Murraya paniculata and Murraya koenigii. Crystals in rays are present in all the species except Clausena excavata and C. lansium. Crystals in parenchyma present in all the genera. Silica bodies occurs in parenchyma in only one species Murraya koenigii and in fibres in Clausena excavata and Murraya koenigii. New reports include coalescent aperture in the entire family. Crystals in fibres of Murraya; crystals in chambered parenchyma of Glycosmis; silica bodies in parenchyma of Murraya koenigii; silica bodies in fibres of Clausena excavata and Murraya koenigii. These features are reported for the first time in this tribe.